Pengaruh Model PBL terintegrasi STEM Dan Motivasi Belajar Terhadap Hasil Belajar HOTS Pada Materi Usaha Dan Pesawat Sederhana - Andriani, Andriani; Pasaribu, Marungkil; Nurjannah, Nurjannah (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
This research aims to test the significance of: (1) differences in learning outcomes students who are treated with an integrated PBL learning model STEM and PBL models; (2) differences in learning outcomes of students who have high learning motivation and low learning motivation; (3) interaction between models learning PBL And motivation Study to results Study participant educate. The population of this study were students in class VIII of SMP Negeri 6 Palu teachings 2023/2024, and the samples in this study were students in class VIII A and class VIII I obtained by purposive sampling. The research instrument consists of a HOTS-oriented learning outcomes test and a Learning Motivation questionnaire. Data analyzed with technique ANOVA two direction. Results Research shows that: (1) there are differences in student learning outcomes who were given treatment between STEM and integrated PBL learning models model PBL Which showed by p-value (0.000) < α (0.05); (2) there is difference motivation Study tall And motivation Study low to results Study which is addressed by the p-value (0.000) < α (0.05); (3) exists interaction between model PBL And motivation based results Study participant educate Which showed by p-value (0.000) < α (0.05).